'Be on the TEAM' Study (Teenagers Against Meningitis): protocol for a controlled clinical trial evaluating the impact of 4CMenB or MenB-fHbp vaccination on the pharyngeal carriage of meningococci in adolescents. Issue 10 (22nd October 2020) - Carr, Jeremy; Plested, Emma; Aley, Parvinder; Camara, Susana; Davis, Kimberly; MacLennan, Jenny M; Gray, Steve; Faust, Saul N; Borrow, Ray; Christensen, Hannah; Trotter, Caroline; Maiden, Martin C J; et al.
Abstract : Introduction: Capsular group B Neisseria meningitidis (MenB) is the most common cause of invasive meningococcal disease (IMD) in many parts of the world. A MenB vaccine directed against the polysaccharide capsule remains elusive due to poor immunogenicity and safety concerns. The vaccines licensed for the prevention of MenB disease, 4CMenB (Bexsero) and MenB-fHbp (Trumenba), are serogroup B 'substitute' vaccines, comprised of subcapsular proteins and are designed to provide protection against most MenB disease-causing strains. In many high-income countries, such as the UK, adolescents are at increased risk of IMD and have the highest rates of meningococcal carriage. Beginning in the late 1990s, immunisation of this age group with the meningococcal group C conjugate vaccine reduced asymptomatic carriage and disrupted transmission of this organism, resulting in lower group C IMD incidence across all age groups. Whether vaccinating teenagers with the novel 'MenB' protein-based vaccines will prevent acquisition or reduce duration of carriage and generate herd protection was unknown at the time of vaccine introduction and could not be inferred from the effects of the conjugate vaccines. 4CMenB and MenB-fHbp may also impact on non-MenB disease-causing capsular groups as well as commensal Neisseria spp. This study will evaluate the impact of vaccination with 4CMenB or MenB-fHbp on oropharyngeal carriage of pathogenic meningococci in teenagers, and consequently the potential for these vaccines to provide broad community protection against MenB disease. Methods and analysis: The 'Be on the TEAM' (Teenagers Against Meningitis) Study is a pragmatic, partially randomised controlled trial of 24 000 students aged 16–19 years in their penultimate year of secondary school across the UK with regional allocation to a 0+6 month schedule of 4CMenB or MenB-fHbp or to a control group. Culture-confirmed oropharyngeal carriage will be assessed at baseline and at 12 months, following which the control group will be eligible for 4CMenB vaccination. The primary outcome is the carriage prevalence of potentially pathogenic meningococci (defined as those with genogroups B, C, W, Y or X), in each vaccine group compared separately to the control group at 12 months post-enrolment, that is, 12 months after the first vaccine dose and 6 months after the second vaccine dose. Secondary outcomes include impact on carriage of: genogroup B meningococci; hyperinvasive meningococci; all meningococci; those meningococci expressing vaccine antigens and; other Neisseria spp. A sample size of 8000 in each arm will provide 80% power to detect a 30% reduction in meningococcal carriage, assuming genogroup B, C, W, Y or X meningococci carriage of 3.43%, a design effect of 1.5, a retention rate of 80% and a significance level of 0.05. Study results will be available in 2021 and will inform the UK and international immunisation policy and future vaccine development. Ethics and dissemination: This study is approved by the National Health Service South Central Research Ethics Committee (18/SC/0055); the UK Health Research Authority (IRAS ID 239091) and the UK Medicines and Healthcare products Regulatory Agency. Publications arising from this study will be submitted to peer-reviewed journals. Study results will be disseminated in public forums, online, presented at local and international conferences and made available to the participating schools. Trial registration numbers: ISRCTN75858406 ; Pre-results, EudraCT 2017-004609-42.